Participation in art and architecture spaces of interaction and occupation - Stierli, Martino 1974- (Bloomsbury Visual Arts, 2022)
Cover -- About the Author -- Endorsement -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgements -- Whose Participation? Introductory Remarks -- Part I: Agency -- 1 The Infrastructure of Participation: Cultural Centres in Postwar Europe -- 2 Occupied Sites: Tlatelolco and Metropol Parasol -- 3 Aesthetics and Politics of Participation in 1960s Brazil: From Hélio Oiticica's Parangolés to the Paulista School of Architecture -- 4 Putting on the Map: Suzanne Lacy's International Dinner Party -- 5 Exhibitions in Damaged and Destroyed Architectural Objects in Besieged Sarajevo: Spaces of Gathering and Socialization -- 6 City of Revolution: On the Politics of Participation and Municipal Management in Cairo -- 7 Disobedient Objects -- Part II: Display -- 8 Between Theatre and Agora: Thoughts on Exhibition, Drama and Participation -- 9 1912 - Hellerau as Spielraum -- 10 Participatory Aesthetics: Alexander Dorner's Reorganization of the Provinzialmuseum Hannover (1923-1926) -- 11 'The Ultimate Erotic Act': On the Performative in Architecture -- 12 Echo-Logy: Working with Allan Kaprow -- 13 Documentary (Non-)Interventions: Mediated Presence in Public Space and its Artistic Reflection -- Author Biographies -- Index
Description based on publisher supplied metadata and other sources
Keywords: Geschichte; Teilhabe; Interaktive Kunst; Ästhetik; Architecture and society; Art-Philosophy; Social participation; Electronic books; Aufsatzsammlung